Kualitas Pelayanan Islami pada Perbankan Syariah - Rafidah Rafidah (NALAR FIQH: Jurnal Hukum Islam, 2014)
Quality of service is one of the elements of assessment of the consumer / customer to the company that is engaged in. Quality services can be realized through the Islamic ministry employees, among others, to be honest, humble service, the service uses the guidelines of Islam, not forgetting the hereafter. Some aspects of this quality when applied together can build excellent quality service and satisfying, so it can be said that the quality of service has considerable influence in determining the interest of the customer to use the services which in this case is to save the Shariah contract.